Adherencia al tratamiento farmacológico y apoyo familiar en pacientes hipertensos atendidos en el centro de salud Daniel Álvarez de Loja - Torres Paqui, Arelis del Cisne (2021)
The adherence to the pharmacological treatment and family support in hypertensive patients take an important role. The lack of adherence in the antihypertensives represents a new challenge for the doctor, due to the right behavior of the patient in front of the therapeutic recommendations will avoid complications, so it is important to value constantly the family support because this is directly proportional to the life quality of the patient. The aims from the present research were to characterize the patients with arterial hypertension diagnosis according to the socio-demographic variables, to identify the adherence to the antihypertensive pharmacological treatment and the family support, also to set the relationship among these variables. A descriptive, observational with quantitative approach and prospective cross-sectional study was made. The population included 147 hypertensive patients that attended to the outpatient clinic service in the “Daniel Álvarez” Health Center in the term from October 2019 - March 2020, through a data collection form and the Morisky Green Levine scale application, and the family support with the Duke UNC scale, the next results were gotten: the 62% (n= 91) are female patients, the 49,7% (n= 73) are older than 65 years, the 35% (n= 52) have high school education, the 29% (n= 42) make household chores, the 80% (n= 118) adhere well and fulfill with the pharmacological treatment, and the 71% (n= 104) receive regular support from the relatives, and the chi-square value was the 11,73, with the p= 0,0006 value, this shows that there is a meaningful statistically combine among the adherence variables to the treatment and family support. Key words: hypertensive, adherence treatment, family support.